The Impact of Work-From-Home Arrangements on Job Satisfaction and Productivity in the Singapore Beverage Company - George Chang Foh Chun; Hemaloshinee Vasudevan (Journal of Management Studies and Development, 2026)
Working from home offers employees greater flexibility and removes commuting time, but it may also create communication barriers, weaken teamwork, and increase feelings of isolation. During the COVID-19 pandemic, many companies adopted work-from-home arrangements to maintain operations while protecting employee health. This study examines the impact of work-from-home practices on finance department staff, with particular attention to job satisfaction, productivity, and changes in work processes. A qualitative research design was employed using semi-structured interviews with selected employees from the Finance Department of Singapore Beverage Company, a mid-sized firm in the beverage sector. Purposive sampling was applied to recruit participants who had worked from home for at least three months, with the final number determined by data saturation. The data were analyzed using thematic analysis to identify recurring patterns and themes. The findings show that employees experienced work from home in different ways, balancing both benefits and challenges. Key themes included mixed levels of job satisfaction, varied productivity outcomes, and contextual factors influencing remote work experiences. The study highlights the importance of flexible and context-sensitive organizational policies. It also suggests that stronger policy support, adequate resources, and clearer work-life boundaries are necessary to improve employee well-being and maintain productivity in remote work settings.